2019 ESC/EAS Guidelines for themanagement of dyslipidaemias: lipid modification to reduce cardiovascular risk - Francois Mach; Colin Baigent; Alberico L. Catapano; Konstantinos C. Koskinas; Manuela Casula; Lina Badimon; M. John Chapman; Guy G. De Backer; Victoria Delgado; Brian A. Ference; Ian M. Graham; Alison Halliday; et al. (Российский кардиологический журнал, 2020)
The Task Force for the management of dyslipidaemias of the European Society of Cardiology (ESC) and European Atherosclerosis Society (EAS)